Radiation induced thyroid cancer: fundamental and applied aspects - Tronko, M.; Bogdanova, T.; Voskoboynyk, L.; Zurnadzhy, L.; Shpak, V.; Gulak, L. (Experimental Oncology, 2010)
Aim: To describe the epidemiology and pathology of thyroid cancer in Ukraine, and to perform the molecular analysis of genetic alterations more frequently found to be associated to papillary carcinomas (PTC) in a selected group of PTC. Materials and Methods: Relationship between the thyroid cancer incidence and gender, age, and place of residence of subjects aged 0–18 years at the time of the Chernobyl accident (5427 subjects of thyroid cancer, among which 3996 (73.6%) were children aged 0 to 14 years at the time of the accident, and 1431 (26.3%) were adolescents aged 15 to 18 years was studied. Pathologically analyzed thyroid carcinomas were obtained from 640 patients (20–40 years old at the time of surgery and born before the Chernobyl accident), and from 90 patients (11–22 years old at the time of surgery and born after the accident). All patients were operated during 2006–2008. RET/PTC rearrangements and BRAFV600E mutation were analyzed in 35 cases of PTC. Results: A comparison between the thyroid cancer incidence rates in the 6 highest contaminated regions of Ukraine and in the other 21 regions shows the most significant difference between the rates for the last three years of follow-up, which confirms that a direct relationship is still present between the rise in thyroid cancer incidence and the post Chernobyl radiation exposure. Much lower incidence of thyroid cancer in subjects, who were born after the accident, additionally confirmed a direct relationship between the Chernobyl accident and thyroid cancer development at least in those who were aged up to 18 years at the time of the nuclear accident. Pathological results showed that with increasing latency the decrease has been noted in the percentage of PTC with solid structure, a decrease in invasive properties of tumors, as well as an increase in the percentage of PTC with papillary-follicular structure, encapsulated forms, and «small» carcinomas measuring up to 1 cm. Molecular-biological studies of PTC revealed more common RET/PTC1 and RET/PTC3 rearrangements (34.3% of cases), than BRAFV600E mutation (24%cases). Conclusion: After 22 years from the Chernobyl nuclear accident the number and incidence of thyroid cancer cases in Ukraine was steadily increased in the cohort of those who were children and adolescents at the time of the accident. Most common thyroid tumors (PTC) were characterized by significant changes in histological structure with increasing latency. PTC with any RET/PTC rearrangements had more aggressive behavior than BRAFV600E-positive tumors or PTC without gene alterations.